The effectiveness of using Quantum Thinker Teaching Model in reading comprehension achievement - Yuniarsi Romaniah; Nike Angraini; Dio Resta Permana (Universitas Muhammadiyah Malang, 2025)
Reading is very prominent to obtain information and influence the learning success. Based on survey results from the last five years, Indonesia has a low level of reading interest. Therefore, the aims of this study were to find out the use of Quantum Thinker Teaching Model in reading comprehension achievement for seventh grade students at SMP Negeri 22 Palembang and the experimental group students’ perception of the use Quantum Thinker Teaching Model. This study used quasi experimental design with the sample were class of VII.2 and VII.6 that consisted of 33 students in each class, and divided into the experimental and control groups. Therefore, the data were collected by using pre-test, and post-test, that analyzed by using paired sample t-test and independent sample t-test with help of SPSS version 27 program. Based on the results of this study, (1) there was significant improvement on students’ reading level category, (2) there was significant improvement in students’ reading comprehension achievement, (3) there was significant improvement in students’ reading aspects, (4) and there was significant mean difference between experimental and control groups. (5) Moreover, the experimental students gave positive perception toward the use of Quantum Thinker Teaching Model in teaching process. In conclusion, the use of Quantum Thinker Teaching Model was improved students’ reading comprehension achievement for seventh grade students.